2017
DOI: 10.1016/j.kint.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Loss of transcriptional activation of the potassium channel Kir5.1 by HNF1β drives autosomal dominant tubulointerstitial kidney disease

Abstract: HNF1β is an essential transcription factor for the development and functioning of the kidney. Mutations in HNF1β cause autosomal dominant tubulointerstitial kidney disease (ADTKD-HNF1β), which is characterized by renal cysts and maturity-onset diabetes of the young (MODY). Moreover, patients suffer from a severe electrolyte phenotype consisting of hypomagnesemia and hypokalemia. Until now, genes that are regulated by HNF1β are only partially known and do not fully explain the phenotype of the patients. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 49 publications
4
55
0
1
Order By: Relevance
“…Mutations in Kcnj16 gene are also associated with nonfamilial Brugada syndrome that causes arrhythmias including sudden cardiac death (26); in addition, genome-wide association studies of metabolite quantitative traits identified Kcnj16 as a candidate gene (27). Furthermore, it was proposed that loss of activation of Kcnj16 by transcriptional factor HNF1β might result in the development of autosomal dominant tubulointerstitial kidney disease (28). Despite these important findings, the mechanistic role of K ir 4.1/K ir 5.1 (Kcnj10/Kcnj16) basolateral K + channels in the development of salt-sensitive (SS) hypertension and control of electrolyte balance is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in Kcnj16 gene are also associated with nonfamilial Brugada syndrome that causes arrhythmias including sudden cardiac death (26); in addition, genome-wide association studies of metabolite quantitative traits identified Kcnj16 as a candidate gene (27). Furthermore, it was proposed that loss of activation of Kcnj16 by transcriptional factor HNF1β might result in the development of autosomal dominant tubulointerstitial kidney disease (28). Despite these important findings, the mechanistic role of K ir 4.1/K ir 5.1 (Kcnj10/Kcnj16) basolateral K + channels in the development of salt-sensitive (SS) hypertension and control of electrolyte balance is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…14,18,19 Recent chromatin immunoprecipitation sequencing (ChIP-seq) experiments have shown that HNF-1b regulates cholesterol metabolism through transcriptional activation of Srebp2 and Pcsk9, 20 urinary concentration through activation of Fxr, 21 and potassium and magnesium homeostasis through activation of Kir5.1. 22 However, the complete gene network governed by HNF-1b in the kidney and the mechanisms whereby human mutations lead to a broad spectrum of clinical phenotypes remain to be fully elucidated. Constitutive ablation of Hnf1b in mice results in embryonic lethality due to failure of endoderm development, 23 and kidney-specific deletion of Hnf1b using the Ksp/Cre deleter strain results in postnatal kidney failure.…”
mentioning
confidence: 99%
“…Immunohistochemistry. Immunohistochemistry (IHC) was performed as previously described (36). In short, stainings for HNF1␤ were achieved on 4-m sections of mouse kidney samples fixed in formalin and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…HNF1␤ is ubiquitously expressed in the epithelial cells of all nephron segments (14). In the distal convoluted tubule (DCT), HNF1␤ regulates the expression of the Kir4.1-Kir5.1 K ϩ channel and the ␥-subunit of the Na ϩ -K ϩ -ATPase (FXYD2) (23,36). Kidney-specific (Ksp) HNF1␤ knockout (KO) mice display reduced Kcnj10 (Kir4.1) and Kcnj16 (Kir5.1) expression levels, resulting in lower Na ϩ -Cl Ϫ -cotransporter (NCC) transcript levels (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation